2021
DOI: 10.3390/biom11070962
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Extracellular miRNA Analysis in Patients with Stable CAD and Acute Coronary Syndromes

Abstract: Extracellular circulating microRNAs (miRNAs) are currently a focus of interest as non-invasive biomarkers of cardiovascular pathologies, including coronary artery disease (CAD) and acute coronary syndromes (ACS): myocardial infarction with and without ST-segment elevation (STEMI and NSTEMI) and unstable angina (UA). However, the current data for some miRNAs are controversial and inconsistent, probably due to pre-analytical and methodological variances in different studies. In this work, we fulfilled the basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…MiR-146a has been shown to be significantly expressed in atherosclerotic arteries ( 32 ). There is also evidence that miR-146a is expressed not only in endothelial cells and smooth muscle cells but also in cardiomyocytes ( 33 ). Etiologies of STEMI include rupture of local vulnerable plaques and cardiomyocyte necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-146a has been shown to be significantly expressed in atherosclerotic arteries ( 32 ). There is also evidence that miR-146a is expressed not only in endothelial cells and smooth muscle cells but also in cardiomyocytes ( 33 ). Etiologies of STEMI include rupture of local vulnerable plaques and cardiomyocyte necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of miR-26a and miR-191 were found in the plasma of individuals with acute MI [111]. Using cDNA synthesis and quantitative PCR, plasma levels of miR-21-5p and miR-146a-5p were significantly elevated in patients with ACS [22]. Expressions of miR-30d-5p, miR-146a-5p, and miR-23a-3p were statistically lower in patients with STEMI compared with the control group patients.…”
Section: Other Mirnasmentioning
confidence: 99%
“…Interestingly, only the combination of miR-146a and miR-21 were independent predictors of LV remodeling [135]. One study reveals that miR-146a-5p is significantly elevated in patients with ACS [22], while on the contrary, miR-146a-5p was also detected statistically lower in patients with STEMI compared with the control group patients [112].…”
Section: Mirna-30 and Mirna-146mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that hsa-miR-17-5p, hsa-miR-20b-5p and hsa-miR-27a-3p co-regulated by these two DElncRNAs have important biological roles in CHD. The expression of hsa-miR-17-5p is down-regulation in patients with CHD, which could be as a biomarker of CHD (Zhelankin et al, 2021) and a good predictor of the severity of coronary atherosclerosis (Chen et al, 2015). In addition, lncRNA SNHG16 could regulate NF-κB signaling pathway by binding hsa-miR-17-5p, and then affect proliferation and inflammatory response in atherosclerosis patients, which provide a potential target for treating AS (An et al, 2019).…”
Section: External Validation Of Ac0100821 and Ac0114431 Using Rt-qpcrmentioning
confidence: 99%